THE ROLE AND IMPORTANCE OF FOREIGN EXPERIENCE IN STRENGTHENING THE REVENUE BASE OF LOCAL BUDGETS - Sharopov Dilshodjon Rakhmatullaevich (European Science Publishing, 2026)
This article analyzes the theoretical and methodological aspects of strengthening the revenue base of local budgets, as well as the experience of foreign countries in this field. In particular, mechanisms such as fiscal decentralization, increasing the share of local taxes, digitalization of tax administration, and diversification of non-tax revenue sources are examined. The study also develops practical recommendations based on institutional factors and the possibilities of adapting advanced foreign practices to national conditions. The research findings contribute to ensuring the financial independence of local budgets and promoting the sustainable socio-economic development of regions.
Keywords: Local budget, revenue base, fiscal decentralization, local taxes, tax administration, non-tax revenues, transfers, budget sustainability, foreign experience, financial independence.